"I wanted to hurt her": Children's and adolescents' experiences of desiring and seeking revenge in their own peer conflicts. Issue 4 (20th February 2019) - Recchia, Holly E.; Wainryb, Cecilia; Pasupathi, Monisha
Abstract: This study examined children's and adolescents' descriptions of wanting and seeking revenge in peer conflicts. A total of 100 youth divided into three age groups (7‐, 11‐, and 16‐year‐olds) were interviewed about experiences in which they wanted to get back at a peer who harmed them. Most youth recalled experiencing retaliatory desires, but typically indicated that such desires were not acted out; 7‐year olds were less likely than older youth to describe carrying out their retaliatory desires. Youths' reasons for seeking revenge versus containing their retaliatory desires revealed age effects in their thinking about their own retaliation. Younger children's reasoning focused on the undesirability of harming others and potential punishments that could ensue, but they generally did not coordinate these concerns with the fact that they themselves had just been harmed. In contrast, older youth described their own retaliatory actions as driven by goals stemming from being deeply hurt, but such goals were balanced against their self‐protective motives, sensitivity to the particularities of transgressions, and self‐reflective moral commitments. Findings underscore that desires for revenge can be considered to be a part of children's experiences of conflict, but also crucially, that youth recognize their own capacities to contain and redirect these desires.